Differential Recognition of Anions with Selectivity towards F− by a Calix[6]arene–Thiourea Conjugate Investigated by Spectroscopy, Microscopy, and Computational Modeling by DFT. Issue 26 (11th May 2016) - Nehra, Anita; Bandaru, Sateesh; Yarramala, Deepthi S.; Rao, Chebrolu Pulla
Abstract: Anion recognition studies were performed with triazole‐appended thiourea conjugates of calix[6]arene (i.e., compound 6 L ) by absorption and 1 H NMR spectroscopy by using nineteen different anions. The composition of the species of recognition was derived from ESI mass spectrometry. The absorption spectra of compound 6 L showed a new band at λ =455 nm in the presence of F − due to a charge transfer from the anion to the thiourea moiety and the absorbance increases almost linearly in the concentration range 5 to 200 μm . This is associated with a strong visual color change of the solution. Other anions, such as H2 PO4 − and HSO4 −, exhibit a redshift of the λ =345 nm band and the spectral changes are associated with the formation of an isosbestic point at λ =343 nm. 1 H NMR studies further confirm the binding of F − efficiently to the thiourea group among the halides by shifting the thiourea proton signals downfield followed by their disappearance after the addition of more than one equivalent of F − . The other anions also showed interactions with compound 6 L, however, their binding strength follows the order F − >CO3 2− >H2 PO4 − ≈CH3 COO − >HSO4 − . The NMR spectral changes clearly revealed the anion‐binding region of the arms in case of all these anions. The anion binding to compound 6 L indeed stabilizes a flattened‐cone conformation as deduced based on the calix‐aromatic proton signals and was further confirmed by VT 1 H NMR experiments. The stabilization of the flattened‐cone conformation was further augmented by the interaction of the butyl moiety of the n Bu4 N + counterion. The structural features of the anion‐bound species were demonstrated by DFT computations and the resultant structures carried the features that were predicted based on the 1 H NMR spectroscopic measurements. In addition, SEM images showed a marigold flower‐type morphology for compound 6 L and this has been transformed into a chain‐like structure of connected spherical particles in the presence of F − . The anion‐induced microstructural features are reflective of the binding strength, size, and shape of the anions. The binding strengths of the anions by compound 6 L were further compared with that of compound 4 L, a calix[4]arene analogue of compound 6 L, in order to address the role of the number of arms built on the calixarene platform based on absorption spectroscopy, 1 H NMR spectroscopy, and DFT computations and it was found that compound 6 L is a better receptor for F −, which extends its interactions from all the three arms. Abstract : Bunch of flowers : The two calixarene‐based triazole‐appended thiourea conjugates 4 L and 6 L were investigated with regard to their anion‐binding ability. Based on spectroscopic methods, DFT calculations, and SEM investigations a binding order for nineteen investigated anions was obtained. F − was found to be best recognized by the composite 6 L (see figure).